Longitudinal determinants of walking, moderate, and vigorous physical activity in Australian adults. - Allen, Mark (My University, 2015)
Objective To explore longitudinal (demographic, socioeconomic, health and psychological) determinants of walking, moderate and vigorous physical activity. Methods The sample included 11,133 adult participants (5913 women; 5220 men) taken from the Household, Income and Labour Dynamics in Australia (HILDA) project. Demographic, socioeconomic, health and psychological data were collected in 2010 and estimates of walking, moderate and vigorous physical activity were collected in 2014. Results Participant age, sex, occupational status, working hours, and neighbourhood remoteness were most strongly related to total physical activity. Psychological traits (personality and distress sensitivity) were unrelated to subsequent physical activity, and health-related behaviours (diet variables and smoking frequency) were moderately related. Participant demographics (age and sex) were most important for vigorous intensity physical activity, and socioeconomic factors (e.g., neighbourhood remoteness, total income, occupational status, weekly hours worked) were most important for moderate intensity physical activity. Conclusions This investigation shows that demographic, socioeconomic, and health-related variables are important determinants of adult physical activity levels, and that demographic and socioeconomic factors might become more or less important for different intensities of physical activity.
Keywords: Health -- Physical activity; Actvities -- Leisure and lifestyle; Health and wellbeing; Actvities; Health; Physical activity; Leisure and lifestyle; Health and wellbeing